2004
DOI: 10.1007/s11103-004-0113-6
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic overexpression of tomato JERF3 in tobacco activates downstream gene expression and enhances salt tolerance

Abstract: The ethylene, jasmonic acid and osmotic signaling pathways respond to environmental stimuli and in order to understand how plants adapt to biotic and abiotic stresses it is important to understand how these pathways interact each other. In this paper, we report a novel ERF protein--jasmonate and ethylene-responsive factor 3 (JERF3)--that unites these pathways. JERF3, which functions as an in vivo transcription activator in yeast, binds to the GCC box, an element responsive to ethylene/JA signaling, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
111
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 43 publications
5
111
1
1
Order By: Relevance
“…What is the relationship of mineral elements (in particular, K + Na + in soils) with root signal transduction (pathways)? Much of former study showed that K + was little connected with anti-drought, but recent research and our results displayed that it was linked with wheat resistance drought [3,7,39,60,66,67,75]. What is the exact soil water stress threshold of individual wheat genotype?…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…What is the relationship of mineral elements (in particular, K + Na + in soils) with root signal transduction (pathways)? Much of former study showed that K + was little connected with anti-drought, but recent research and our results displayed that it was linked with wheat resistance drought [3,7,39,60,66,67,75]. What is the exact soil water stress threshold of individual wheat genotype?…”
Section: Discussionmentioning
confidence: 78%
“…Many advances in relation to this hot topic, including molecular mechanism of anti-drought and corresponding molecular breeding have taken place [28,33,34,39,44,47,50,53,[55][56]63,[72][73][74][75]78]. Although the obtained transgenic crops (mainly, wheat) by different types of gene technology all exhibit drought resistance to some extent, they have many shortfalls related to agronomical performance and/or development [47,49,53,62,66,68,74]. These results imply that systemical, deeper, and comprehensive understanding of physiological mechanism of crops under drought stresses is not enough to manipulate the physiological regulatory mechanism and take advantage of full this potential for productivity, whose study is the bridge between molecular machinery of drought and anti-drought agriculture, because the performance of genetic potential of crops is expressed by physiological realization in fields [1,2,8,10,53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Drought is a complex physical-chemical process, in which many biological macromolecules and small molecules are involved, such as nucleic acids (DNA, RNA, microRNA), proteins, carbohydrates, lipids, hormones, ions, free radicals, mineral elements [3,8,12,13,18,20,22,26,31,43,49,50,55,65]. In addition, drought is also related to salt stress, cold stress, high temperature stress, acid stress, alkaline stress, pathological reactions, senescence, growth, development, cell cycle, UV-B damage, wounding, embryogenesis, flowering, signal transduction and so on [16,17,[26][27][28]36,37,[44][45][46][47][52][53][54]62]. Therefore, drought is connected with almost all aspects of biology.…”
Section: Introductionmentioning
confidence: 99%
“…Just 2 years ago, European Commission, who once kept conservative to biotechnological breeding, constructed a big project: Plants for the Future in which much is involved in resistance drought [5]. Many advances in relation to this hot topic, including molecular mechanism of antidrought and corresponding molecular breeding have taken place [4,10,16,17,21,[23][24][25]30,31,35,37,39,42,48,[55][56][57][58][59]. Although the obtained transgenic crops (mainly, wheat) by different types of gene technology all exhibit resistance drought to some extent, they have many shortfalls related to agronomical performance and/or development [1,16,17,21,24,30,39,49,56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation